Let the Market Decide: An Experimental Study of Competition and Fairness - Björn Bartling; Manuel Grieder; Christian Zehnder (Center for Economic Studies and ifo Institute (CESifo), 2014)
Is competition perceived as a fair procedure? We report data from laboratory experiments where a powerful buyer can trade with one of several sellers. Sellers who feel shortchanged can engage in counterproductive behavior to punish the buyer. We find that the same unfavorable terms of trade trigger significantly less punishment if the buyer uses a competitive auction to determine the terms of trade than if she uses her authority to dictate the same terms directly. Our results inform the debate on the fairness of market outcomes by showing that the use of a competitive procedure can, by itself, affect how people judge unequal distributive outcomes.
Keywords: C91; D03; D63; 330; competition; authority; markets; fairness; responsibility; procedures